Inpatient migration patterns in persons with spinal cord injury: A registry study with hospital discharge data - Elias Ronca; Anke Scheel-Sailer; Hans Georg Koch; Stefan Metzger; Armin Gemperli (Elsevier, 2016)
This study investigated and compared patient migration patterns of persons with spinal cord injury, the general population and persons with morbid obesity, rheumatic conditions and bowel disease, for secondary health conditions, across administrative boundaries in Switzerland. The effects of patient characteristics and health conditions on visiting hospitals outside the residential canton were examined using complete, nationwide, inpatient health records for the years 2010 and 2011. Patients with spinal cord injury were more likely to obtain treatment outside their residential canton as compared to all other conditions. Facilitators of patient migration in persons with spinal cord injury and the general hospital population were private or accidental health insurances covering costs. Barriers of patient migration in persons with spinal cord injury were old age, severe multimorbidity, financial coverage by basic health insurance, and minority language region. Keywords: Spinal cord injury, Patient migration, Health services accessibility, Health care utilization, Inpatient hospital care